Pengembangan Literasi Digital Masyarakat Sekolah Melalui Pelatihan Pembuatan Komik Digital Cerita Rakyat - Deswalantri Deswalantri; Ika Wahyu Pratiwi; Apriani Riyanti; Ilma Wulansari Hasdiansa; Sitti Hasbiah (PT. Global Research Collaboration, 2023)
This community service activity aims to increase the level of digital literacy among school community members, especially teachers and students, through the development of folklore in the form of digital comics using the Canva application. The approach in the implementation of this PKM involves training and guidance activities for participants, helping them master the use of the Canva application to create folktales in digital comic format. During the training period, participants were provided with detailed guidance on techniques to visually depict folklore, incorporate it with digital technology, and present it in an attractive comic format. In addition, participants were also equipped with knowledge on utilizing social media and other digital platforms as a means to share the works they have created. The outcomes of this activity include a significant improvement in participants' digital literacy skills, increased appreciation for local cultural heritage through folklore development, and increased creativity in the utilization of digital technology. Therefore, this PKM has a positive impact in supporting the improvement of digital literacy, promoting appreciation of local cultural heritage through digital platforms, and providing active opportunities for school communities to participate more proactively in the evolving digital era.